DAMPAK OPERASI PASAR MODERN TERHADAP PENDAPATAN PEDAGANG PASAR TRADISIONAL DI KOTA PEKALONGAN - Dwi Susilo (LPPM Universitas Pekalongan, 2011)
Generally, the operation of modern market at Pekalongan city has impact towards tradisional market. The aim of this research is to detect the impact of modern market operation towards traditional market tradesman income. The sample of the research are 150 tradesman at traditional market that predicted has an impact from modern market “Sri Ratu Mega Center/Carrefour Pekalongan”. The analysis model is two related sample comparation by using the wilcoxon sign test for detected the difference of traditional market tradesman income before operation and after operations the modern market at Pekalongan city. The analysis show that data have not normal distribution (cause the kolmogorov smirnov test has the value asymp sig (2-tailed) less than 0,05, and the wilcoxon sign test value asymp sig (2-tailed) 0,00 less than 0,05. The result show that the traditional market tradesman income has the difference among before and after operation of modern market Althoughtthere is a difference income, but in detail, only 39 tradesman (from 150 sample) have influenced by modern market, and 111 tradesman have no in influenced. The conclusion is the operation of modern market at Pekalongan has no influencing to traditional market tradesman income, and therethe reality that “temporary market” have more influence The keyword Traders Market Modern, Traditional Markets, Income